Fibrous scaffolds from PCL/Chitosan blends for tissue engineering - Pereira, Andreia Leal (2018)
The development of artificial structures (scaffolds), that mimic the extracellular matrix as closely as possible, and that aid in the regeneration of living tissues, has been one of the main areas of study in tissue engineering. Two-dimensional nanofibrous can be obtained by electrospinning, but three-dimensional structures are very difficult to obtain directly by electrospinning. Because of that, a group of researchers recently developed a technique called Thermally Induced Self-Agglomeration (TISA) that allows transforming two-dimensional electrospun membranes into three-dimensional structures. The objective of this work was to produce and characterize electrospun membranes of PCL/chitosan blends, to then convert them into 3D structures by TISA, followed by freeze drying. The obtained products were nanofibrous 3D scaffolds with increasing amounts of chitosan (10, 15 and 20%), highly porous (>90%) and with interconnected pores of different sizes. Compression modulus indicated compatibility for cartilage tissue engineering. The results demonstrated that the obtained scaffolds presented high similarity both in morphology and properties to the natural extracellular matrix. Therefore, its application in tissue engineering should be very promising